PERANCANGAN ANIMASI CERITA WAYANG SEBAGAI MEDIA PEMBELAJARAN PADA SISWA KELAS V SD NEGERI KUTOSARI 02 GRINGSING - Ary Setiaji (Pixel :Jurnal Ilmiah Komputer Grafis, 2017)
This study aims to design learning media that can increase enthusiasm, motivation, and understanding of students, and can facilitate teachers in learning Javanese subjects with material listening to the Werkudara puppet story. The method used in research is R&D (Research and Development) while the method used in the development of instructional media is the waterfall method. The story developed is a story with the title (1) Butcher Bilawa, (2) Bima Bungkus, and (3) Bima Suci. To produce a learning media researchers use a design processing program including; Adobe Photoshop CC, Adobe After Effects CS6, Adobe Audition CS6, Pinnacle Studio 16, Adobe Flash CS6 with the final product in the form of an interactive CD. The results of the assessment by media experts and material experts, get the criteria value "quite good" - "very good" and tend to approach the criteria of "very good", while the results of the final product trial evaluation by students shows that all students totaling 23 children "agree" - "strongly agree" and approach the "strongly agree" category with the use of developed learning media. Thus the learning media for puppet story animation was declared feasible to facilitate learning activities in Javanese subjects to listen to the Werkudara puppet story in fifth grade students of Kutosari 02 State Elementary School.